Creative Abilities and Incubation: The Poincaré Effect - E.A. Valueva; D.V. Ushakov (Экспериментальная психология)
Incubation is a period during which a subject temporarily makes no conscious attempts to solve a problem but eventually arrives at a solution. Henri Poincaré described cases where insights came after a break from working on complex mathematical problems. This article proposes a hypothesis called the «Poincaré effect»: the higher a person's creativity, the more pronounced the effect of incubation in their creative process. An experimental study was conducted with 525 participants divided into a control group (without incubation) and an experimental group (with an incubation break). Participants performed the «Alternate Uses» test, inventing non-standard ways to use a matchstick. Creativity was assessed based on fluency (the number of ideas) and originality. The results showed that the incubation break led to a significant increase in the fluency of responses in the experimental group. Moreover, among participants with a high level of creativity, incubation contributed to an increase in the originality of responses, confirming the Poincaré effect. These findings align with the awareness model, according to which incubation helps restructure the problem representation and recognize previously found unconscious solutions. The study's conclusions confirm the presence of the Poincaré effect in the phenomenon of incubation and highlight the importance of individual creative abilities in the problem-solving process.